LANDCOVER CHANGES IN COASTAL BUNGUS REGION OF KABUNG BAY, WEST SUMATRA FROM 200-2013 BASED ON GEOGRAPHIC INFORMATION SYSTEM APPLICATION - Yulius Yulius; T A Tanto; M Ramdhan; A Putra; H L Salim (Jurnal Ilmu dan Teknologi Kelautan Tropis, 2014)
ABSTRACT Bungus district of Kabung Bay is a growing region located at coastal zone of southern city of Padang, west sumatra. As a growing region, the Bungus district brings some impacts on population increase and degradation of environment quality. Therefore, it is needed an effort to identify land use changes and the distribution of land use in this region from the year of 2003 until 2013. This research used landsat 7 imagery in 2003 and landsat 8 imagery in 2013. The data were analysed descriptively using geographical informastion system. The result showd that (1) swamp land cover experienced the smallest land use change between 2003 until 2013 (0.02 ha/yr), meanwhile forest land use had the biggest change of about 224.8 ha/yr. The biggest addition of land cover belong to settlement area about 47.59 hectare, and the other hand occur on bush about -31.68 hectare. Keywords: Bungus district, landcover changes, Landsat imagery, GIS